AN ATYPICAL PRESENTATION OF BREAST CARCINOMA HER2 - Queiroz, Lais Martins; Perillo, Pedro Henrique Ávila; Santos, Vinicius Catenassi Pereira; Câmara, Maria Carrijo Cunha; Costa, Lyna Maria Alves da; Azevedo, Fernando Santos de; Santana, Lanúscia Morais de (Mastology, 2021)
Introduction and Objectives: HER-2 overexpression occurs in 20% to 30% of invasive breast carcinomas. Even in localized disease, it is considered aggressive and can spread rapidly if not treated early. This report depicts the case of a patient with Luminal HER breast cancer with extensive cutaneous and lymph node disease, without visceral metastasis. Case Report: A 58-year-old woman with a lesion in the anterior thoracic region, ulcerated, painful, and friable to manipulation, with approximately 13 cm in the largest axis, initially diagnosed as dermatofibrosarcoma protuberans. The lesion evolved with rapid progression in size, 17 cm in the longest axis, and was re-biopsied, revealing invasive breast carcinoma with positive immunohistochemistry for ER (90%), RP (50%), HER2+ (3+), positive FISH, and Ki67 (20%). Staging examinations, extensive disease in the anterior thoracic region and right lymph node, other examinations were negative for visceral metastatic disease. Discussion: This case presents an atypical evolution of Luminal HER breast carcinoma in which the unusual clinical presentation delayed diagnosis. Unlike the identified common presentation, in this case, an extensive ulcerated and friable lesion on the anterior chest wall with extensive cutaneous and lymph node involvement is observed. Furthermore, we emphasized the relevance of the pathological findings for the correct identification of the tumor, since after reanalysis, the diagnosis of dermatofibrosarcoma protuberans was disregard, and the presence of molecular breast carcinoma subtype luminal HER was identified, which brings changes in prognosis and therapy. Conclusion: Therefore, a completely atypical manifestation of a luminal malignant HER mammary neoplasm, without visceral disease, is perceived. Furthermore, the importance of the clinical and pathological findings in the diagnosis and therapeutic management for the case resulting from atypical clinical manifestations is emphasized. Therefore, the importance of this report to expose a completely anomalous manifestation of breast cancer, which without a good investigation would receive incorrect treatment, is noted.